Decoding Bioeconomy: Trends and Definitions Through Bibliometric Insights - Momete, Daniela Cristina (European Journal of Sustainable Development, 2025)
Bioeconomy is a field of study with major importance for economic systems, but its conceptualization still lacks a harmonized definition. To address this challenge and contribute to the understanding of the field of bioeconomy, the present research aims to identify the newest research tracks in the field of bioeconomy by conducting a bibliometric study within the interval 2010-2024. The aim of the paper is to grasp all the relevant literature streams over the recent period by employing Dimensions as a database, with the aim to better define bioeconomy. The results are analyzed and visualized with the help of the VOSviewer software for term co-occurrence maps, co-authorship based on authors, institutions, countries and journals. The findings of this paper may be valuable for researchers, academia, and policy makers interested in consolidation of the bioeconomy model to render a comprehensive system where bioeconomy can be better understood, defined and measured Keywords: bioeconomy, sustainable development, bibliometrics, circular economy